A role for PFKFB3/iPFK2 in metformin suppression of adipocyte inflammatory responses. (July 2017) - Qi, Ting; Chen, Yanming; Li, Honggui; Pei, Ya; Woo, Shih-Lung; Guo, Xin; Zhao, Jiajia; Qian, Xiaoxian; Awika, Joseph; Huo, Yuqing; Wu, Chaodong
Abstract : Metformin improves obesity-associated metabolic dysregulation, but has controversial effects on adipose tissue inflammation. The objective of the study is to examine the direct effect of metformin on adipocyte inflammatory responses and elucidate the underlying mechanisms. Adipocytes were differentiated from 3T3-L1 cells and treated with metformin at various doses and for different time periods. The treated cells were examined for the proinflammatory responses, as well as the phosphorylation states of AMPK and the expression of PFKFB3 /iPFK2. In addition, PFKFB3 /iPFK2-knockdown adipocytes were treated with metformin and examined for changes in the proinflammatory responses. The following results were obtained from the study. Treatment of adipocytes with metformin decreased the effects of lipopolysaccharide on inducing the phosphorylation states of JNK p46 and on increasing the mRNA levels of IL-1β and TNFα. In addition, treatment with metformin increased the expression of PFKFB3 /iPFK2, but failed to significantly alter the phosphorylation states of AMPK. In PFKFB3 /iPFK2-knockdown adipocytes, treatment with metformin did not suppress the proinflammatory responses as did it in control adipocytes. In conclusion, metformin has a direct effect on suppressing adipocyte proinflammatory responses in an AMPK-independent manner. Also, metformin increases adipocyte expression of PFKFB3 /iPFK2, which is involved in the anti-inflammatory effect of metformin.